Chrono-modulated effects of external stressors on oxidative stress and damage in humans: A scoping review on night shift work - Makris, Konstantinos C.; Heibati, Behzad; Narui, Shan Zienolddiny (My University, 2023)
Oxidative stress and tissue damage (OSD) play a pivotal role as an early-stage process in chronic disease pathogenesis. However, there has been little research to better understand the temporal (χρόνος[chronos]) dimensions of OSD process associated with environmental (non-genetic, including behaviors/lifestyle) and/or occupational stressors, like night shift work. OSD processes have recently attracted attention in relation to time-resolved external stressor trajectories in personalized medicine (prevention) initiatives, as they seem to interact with circadian clock systems towards the improved delineation of the early stages of (chronic) disease process.
Keywords: Chronobiology; Circadian disruption; Critical life stage; Diurnal; Oxidative stress; Personalized medicine; Personalized prevention; Precision medicine; Shift work